UPAYA BADAN KETAHANAN PANGAN KABUPATEN ROKAN HILIR DALAM MENGOPTIMALISASIKAN KETERSEDIAN PANGAN TAHUN 2011– 2013 - Sarpika, Dewi; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Food security is the agricultural sector, which has a strategic role in the development of the regional economy. Kabupaten Rokan Hilir is the largest rice production to reach 50-55% in Riau. Badan Ketahanan Pangan to seek sustainable food security through programs that try stability of rice back. Based on the Law of the Republic of Indonesia Number 18 Year 2012 on Food. Article 41 which reads